2016
DOI: 10.1039/c6ra23007e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0) nanoparticles supported on polydopamine coated Fe3O4 as magnetically isolable, highly active and reusable catalysts for hydrolytic dehydrogenation of ammonia borane

Abstract: Palladium(0) nanoparticles supported on polydopamine coated magnetic ferrite nanopowders are highly active and reusable catalyst in hydrogen generation from the hydrolysis of ammonia borane with a turnover frequency of 14.5 min−1 at 25.0 ± 0.1 °C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Additionally, the bands ascribed to Pd (II) 3d 3/2 and 3d 5/2 appear at 341.5 eV and 336.4 eV, respectively. The existence of Pd (II) species is because parts of Pd NPs are oxidized in air …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the bands ascribed to Pd (II) 3d 3/2 and 3d 5/2 appear at 341.5 eV and 336.4 eV, respectively. The existence of Pd (II) species is because parts of Pd NPs are oxidized in air …”
Section: Resultsmentioning
confidence: 99%
“…The existence of Pd (II) species is because parts of Pd NPs are oxidized in air. 24 Three main weight loss stages can be observed in the thermogravimetric (TG) curve of Pd(0)/g-C 3 N 4 -CS ( Figure 5). The first one lower than 100°C comes from the water-adsorbed evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 1720, 1770, and 1370 cm −1 corresponded to the COOH, CONH, and CN stretching vibrations, respectively. After the PDA was modified on the PI membrane surface, some peaks appeared at 1615, 1271, and 1057 cm −1 ; these corresponded to the CN, CN and OH stretching vibrations, respectively, of PDA and suggested the formation of PDA on the PI membrane surface. In contrast, the peaks at 1211 and 1155 cm −1 were attributed to the symmetric and antisymmetric stretching vibration absorption peaks of CF 2 in PTFE; this indicated that the PTFE particles were successfully adhered to the PI membrane.…”
Section: Resultsmentioning
confidence: 99%
“…A volume of 0.40 mL of 28–30 wt % ammonia aqueous solution (NH 4 OH) was added to 100 mL of and EtOH/H 2 O mixture (3:7 v/v). Then, 0.2 g of dopamine hydrochloride was subsequently added to the previous solution and stirred at room temperature until we obtained the PDA solution …”
Section: Methodsmentioning
confidence: 99%
“…[9][10][11] Conversely, of the various hydrogen storage approaches, such as metal hydrides, sorbentm aterials, and chemical hydride materials, ammonia borane (NH 3 BH 3 ,A B) with ah ighg ravimetric hydrogen density (19.6 wt %) and favorable kinetics for hydrogen release, has recently received great attention. [12][13][14][15][16][17][18] Currently,n oblemetal catalysts are considered to be state-of-the-art HER and AB hydrolysis catalysts, however,t heir widespread applications have been severelyh indered by their high cost and scarcity. [19,20] Therefore, the development of efficient earth-abundant catalysts for HER and AB hydrolysis as alternatives to noble metals is highly desirable, but still remains ah uge challenge.…”
Section: Introductionmentioning
confidence: 99%